IMPLEMENTASI PRINSIP-PRINSIP AHLUSUNNAH WAL JAMA'AH PADA MATA PELAJARAN PAI DALAM MEMBENTUK KARAKTER PESERTA DIDIK KELAS XI SMA ISLAM AL-MAARIF SINGOSARI - Reza Anggita Nia; Eko Nasrullah; Dian Mohammad Hakim (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study discusses the implementation of the principles of Ahlusunnah wal Jamaah in PAI subjects in shaping the religious character of students at Al-Maarif Singosari Islamic High School. This research is motivated by how to shape the religious character of students with the principles of aswaja. The method used in this research is a qualitative research with a case study method with interview, observation, and documentation techniques, then finally the researcher gets the information needed. After finding the results, the researcher analyzed the data by means of data collection, data reduction and data verification. The results of this study show how the planning process of the implementation of the principle of aswaja, the implementation of the principle of aswaja and evaluation of the implementation of the principle of aswaja. In order to find out how the impact of applying the principle of Aswaja in shaping the character of students.